Research on influence of modification on structure and mechanical properties of manganese-iron brass CuZn40Mn3Fe - Romankiewicz, Remigiusz; Romankiewicz, Ferdynand (Wydawnictwa AGH, 2017)
Research on the modification of manganese-iron brass CuZn40Mn3Fe with the use of variable additions of titanium and boron have shown that these additives cause fragmentation (refinement) of the structures (grains and precipitates of phase a) and an increase in the amount of precipitations of phase a in the brass structure. As a result of this modification, growth in the brass impact resistance (from 40 J/cm2 to 46-48 J/cm?) and tensile strength (from 400 MPa to 509 MPa) are achieved.

Badania nad modyfikacją mosiądzu manganowo-żelazowego CuZn40Mn3Fe zmiennymi dodatkami tytanu i boru wykazały, że dodatki te powodują rozdrobnienie struktury (ziarn i wydzieleń fazy a) oraz zwiększenie w strukturze mosiądzu ilości wydzieleń fazy a. W efekcie modyfikacji osiągnięto wzrost udarności mosiądzu z 40 J/cm2 do 46-48 J/cm? oraz wytrzymałości na rozciąganie z 400 MPa do 509 MPa.
Badania wpływu modyfikacji na strukturę i właściwości mechaniczne mosiądzu manganowo-żelazowego CuZn40Mn3Fe
Metallurgy and Foundry Engineering
Bibliogr. s. [139].
Keywords: modification; structure; mechanical properties; manganese-iron brass; modyfikacja; struktura; właściwości mechaniczne; brąz manganowo-żelazowy